CULTURAL AND ENVIRONMENTAL INFLUENCES ON SCHOOL BUILDING DESIGN: A COMPARATIVE STUDY BETWEEN THAILAND AND INDONESIA (CIVIL ENGINEERING PERSPECTIVE) - Setiawan, Agus; Carina, Annisa’; Yuniar Caroline, Vanezia; Dueramaeng, Wael (SAINTIS Jurnal ilmu-ilmu eksakta, 2025)
This study examines how cultural and environmental factors influence school building design in Thailand and Indonesia from a civil engineering perspective. The research focuses on the relationship between local traditions, climatic conditions, and structural design principles used in educational facilities. Field observations were conducted at SriChiwan Wittaya School in Yala, Thailand, and compared with similar public schools in East Java, Indonesia. The study employed a qualitative comparative method supported by structural analysis, environmental assessment, and documentation review. Findings indicate that Thailand’s school designs adopt more climate-responsive features such as elevated foundations, cross-ventilation, and lightweight roof systems to adapt to tropical weather and flooding conditions. In contrast, Indonesia’s schools prioritize structural rigidity using reinforced concrete frames and heavy roofing, influenced by cultural perceptions that equate strength with durability. Environmental adaptation in Thailand is enhanced by national design guidelines emphasizing sustainability and energy efficiency, while in Indonesia, such implementation remains limited due to cost and policy constraints. The study concludes that integrating environmental engineering approaches with local cultural understanding is essential to achieve sustainable, resilient, and contextually appropriate school designs in Southeast Asia.